Double Arcus Senilis: Doi:10.36351/pjo.v36i4.884 - Nadeem, Sana (Pakistan Journal of Ophthalmology, 2020)
Arcus senilis is the commonest of the corneal degenerations and presents as a whitish or yellowish band in the corneal periphery, associated with the deposition of lipoproteins in the corneal stroma. It is separated from the limbus by a clear zone. It is most commonly associated with aging. Other associations are hyperlipidemia, particularly in men less than 50 years (arcus juvenilis). However, a double arcus is very rare and only few case reports are found in literature. I present a case of 68-year-old man with diabetes mellitus and 35 pack years of smoking who presented to us in the Out Patient Department. He had double corneal arcus in both eyes. There was a distinct clear line between the two arci. The case is presented with a brief discussion on the traditional risk factors, possible pathogenesis and literature review. Key Words: Arcus senilis, Gerontoxon, Arcus Juvenilis.